1975
DOI: 10.1071/ar9750173
|View full text |Cite
|
Sign up to set email alerts
|

The effect of soil water on root production of peach trees in summer

Abstract: The effect of soil water supply on peach root production in summer was studied in the Goulburn Valley area of northern Victoria. Under commercial irrigation practice roots do not grow in summer. Field experiments showed that when the soil was kept moist by frequent irrigation (every 3–4 days), the concentration of roots in the surface soil nearly doubled in a single season. Furthermore, observation through glass plates showed that this enhanced root growth occurred throughout summer. When roots were kept inact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

1980
1980
2008
2008

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…Various attempts have been made to describe root foraging responses to soil moisture heterogeneity (Richards & Cockroft, 1975; Coutts, 1982; Fort et al ., 1998; Green & Clothier, 1999; Steudle, 2000); however, we are unaware of any studies that have evaluated the role of a plant's potential growth rate. Using a system where genetically identical shoots were grafted on to two genetically diverse root systems, one of known high growth potential (HSV) and one of lower growth potential (LSV), we provide evidence that growth predisposition influenced root responses in both space and time across a gradient in plant water stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various attempts have been made to describe root foraging responses to soil moisture heterogeneity (Richards & Cockroft, 1975; Coutts, 1982; Fort et al ., 1998; Green & Clothier, 1999; Steudle, 2000); however, we are unaware of any studies that have evaluated the role of a plant's potential growth rate. Using a system where genetically identical shoots were grafted on to two genetically diverse root systems, one of known high growth potential (HSV) and one of lower growth potential (LSV), we provide evidence that growth predisposition influenced root responses in both space and time across a gradient in plant water stress.…”
Section: Discussionmentioning
confidence: 99%
“…During periods of decreased water availability, increased root production or fine lateral initiation has been observed in field‐grown tomatoes (Reid & Renquist, 1997) and perennial ryegrass ( Lolium perenne ; Jupp & Newman, 1987). As soil dries, plants typically reduce root growth (Richards & Cockroft, 1975; Steudle, 2000; Comas et al ., 2005) and carbon allocation (Kosola & Eissenstat, 1994) to those roots in dry portions of soil and preferentially grow roots in regions of high soil moisture (Coutts, 1982; Fort et al ., 1998; Green & Clothier, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…During the period between budburst and leaf senescence, I*"'' was the critical factor controlling RER. Deans (1979), Roberts (1976), and Richards and Cockroft (1975) reported that root growth tended to decrease with decreasing soil moisture even in periods when soil temperature was increasing. Root growth of white oak was similar except that soil water deficits in the range of -0.4 to -0.8 MPa induced greater root production than did higher levels of f'^"'' which produced high RER but low NR.…”
Section: Discussionmentioning
confidence: 99%
“…It is fairly well known that root growth in temperate fruit trees exhibits strong seasonal periodicity and can be affected by crop load (Atkinson, 1980). Peach appears to be no exception, and several researchers have reported clear peaks of root growth in the spring and after harvest but there is some controversy over whether the peaks in root growth are coordinated with periods of shoot growth, crop demands for assimilates or soil growth conditions (Richards and Crockroft, 1975;Williamson and Coston, 1989;Glenn and Welker, 1993). Furthermore, the goal of all the previous peach studies was to describe the natural patterns of root growth under field conditions using root observation boxes or mini-rhizotrons but not necessarily to quantify root growth potential.…”
Section: Introductionmentioning
confidence: 99%